Bringing Conservation to Cities : Lessons from Building the Detroit River International Wildlife Refuge - Hartig, John H., 1952- (Ecovision world monograph series., 2018)
There is growing interest in re-connecting urban residents with nature, but most conservationists want to work in pristine areas, and most urban areas are considered too degraded to rank high on conservation priority lists. Bringing Conservation to Cities is a timely and informative expose of what it takes to foster a conservation ethic in a major urban area--complete with critical lessons learned--and to simultaneously inspire and develop the next generation of urban conservationists. The book explores the new urban conservation frontier, with its numerous challenges and opportunities, and fosters more urban conservation initiatives throughout the world.